Upaya Meningkatkan Hasil Belajar Siswa Kelas VII Pada Materi Kebhinekaan Indonesia Dengan Metode Sosiodrama Di SMP Negeri 40 Surabaya - Dwi Purwanti; Akhmad Qomaru Zaman; Suhartono Suhartono (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2023)
Communication space in social life is increasingly limited because we rarely see other people, and everyone will become individualist and less socially sensitive. There needs to be strengthening through sociodrama-based PPKn learning on diversity material to strengthen the sense of unity and unity between.. The purpose of this Classroom Action Research (PTK) is to improve learning outcomes on Indonesian diversity material with the sociodrama method of grade VII-E students in the even semester of the 2022/2023 academic year at SMP Negeri 40 Surabaya. The subject of research is students. Data collection using test and non-test techniques. The data analysis technique uses qualitative data analysis and quantitative data analysis. The results showed that there was an increase in learning outcomes on average 59.5 in the first cycle to 77.3 in the second cycle. For the highest value of 79 in the first cycle to 90 in the second cycle. As well as the value in the first cycle 30 in the first cycle to 62 in the second cycle. The sociodrama method can improve PPKn learning outcomes in Indonesian diversity material for grade VII-E students in the 2022/2023 academic year at SMP Negeri 40 Surabaya.